Гіпоглікемічний ефект полісахаридів, виділених з пагонів Actinidia arguta - Niu, Qiang; Shen, Jian; Li, Lili; Zhang, Huiming; Zaimenko, Natalia; Skrypchenko, Nadiia; Tian, Lijuan; Sun, Honglai; Wang, Lihong; Liu, Dejiang (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2022)
Diabetes mellitus can result in hyperglycemia caused by insufficient insulin secretion or insulin resistance. As such, plant extracts that exert a hypoglycemic effect with limited side effects are of interest to the medical and healthcare fields. The hypoglycemic effect of polysaccharides extracted from the branches of Actinidia arguta was explored in mice in this study. Sixty male Kunming mice were subsequently randomly assigned to one of six groups. The body weight, fasting blood glucose level, serum lipids, and oxidative stress parameters were assessed weekly during the 28-day study period. Pancreatic tissue from sacrificed mice was harvested at the end of the study and dissected for analysis. Polysaccharide AABP3 prevented body weight loss and decreased the fasting blood glucose level in diabetic mice compared with control mice. It also had a beneficial effect on serum dyslipidemia and oxidative stress parameters and was comparable in its protective effect to metformin. Histopathological examination of the pancreas revealed that AABP3 could protect and ameliorate pancreatic damage that may occur in diabetes mellitus in mice. AABP3 may be considered a potential candidate for developing a functional food or natural product for treating diabetes and its complications.